Idealisasi Badan Pembinaan Ideologi Pancasila dalam Sistem Ketatanegaraan Indonesia (Analisis Yuridis Terhadap Peraturan Presiden Nomor 7 Tahun 2018 tentang BPIP) - Yassir Arafat (LP3M KH Yazid Karimullah Institute, 2022)
To re-actualize the values ​​of Pancasila, President Joko Widodo has issued Perpres BPIP which is a refinement of the UKP-PIP. This study aims to analyze (1) the position of the Pancasila Ideology Development Agency in the Indonesian constitutional system and (2) the idealization of the Pancasila Ideology Development Agency in the Indonesian constitutional system. The research method used in this research is the normative juridical method. To answer the existing legal issues as scientific processing, it is doctrinal which uses deductive logic by using primary legal materials and secondary legal materials. The results of this study indicate that (1) the position of the BPIP in the Indonesian constitutional system is a non-ministerial institution that assists the President's duties in Pancasila Ideology Development; and (2) Considering the important role of BPIP in re-actualizing the values ​​of Pancasila, ideally BPIP should be formed based on a separate law. The goal is to strengthen BPIP institutionally so that its presence is not only at the center but also has representatives at the provincial level to the district or municipal level. So that in carrying out their duties and functions more systematically and optimally.